The torsion of the multicell sections - Marcel STERE (INCAS Bulletin, 2010)
The paper is focused on the stress analysis of thin-walled multicell sections subjected to pure torsion. The shear flow and stiffness characteristics of the cross section for torsion are given. Example: aircraft wing section. The theory for thin-walled closed sections used in this paper was developed by Bredt [3]. The shear flows obtained are used in the design of skins and interior webs, ribs and fasteners at skin splices, skin web junctions and the joints where the ribs meet the skin or webs.